Editorial - Editor (Hamdard Islamicus, 2021)
The current issue presents three research based articles, a book review and obituary. Prof. Dr. Thameem Ushama (Malaysia) has thoroughly discussed the takfÊrÊ problem faced by the Muslim states in the current period in his article “Radical Muslim Fringe Groups’ Recourse to TakfÊr (Accusing Muslims of Infidelity): A Critique”. The article also provides a way-out of this grave crisis. Dr. Nasim Razi (Pakistan) has compared and discussed the Islamic Law and Common Law in her article “Islamic Law vis-à-vis Common Law: A Historical Analysis in Terms of Rigidity and Flexibility”